COVID-19 and the state of mental health challenges among Women, Girls and Children: the case of Nigeria - Etinosa, Egharevba Matthew; Gbadebo, Adejumo Olubunmi; Olawale, Olonade Yunusa; Oke, Ugbenu; Gayus, Kasa Adamu (Advances in Social Sciences Research Journal, 2022)
Health is a resource for daily existence and wellbeing. Mental, social, emotional, spiritual, psychological and physical health constitute an overall essence of that well-being. The COVID-19 epidemic has had a profoundly negative impact on women, children, and society as a whole by causing unfathomable loss, grief, pain, and solitude. The pandemic has pushed many families into poverty and exacerbated conditions of inequality with women and children exposed to violence and other deprivation which deeply impacted on their mental health. The study employed the use of content analysis of secondary sources of data, and the social stress, social model and general strain theories constituting the theoretical framework for examining the subject under investigation. The findings of the study demonstrated that the prevalence of mental disorders among women and children is rising, with serious human rights and socio-economic repercussions as a result of poverty and gender inequality. Furthermore, the majority of those suffering from mental health issues are unable to get the crucial medical and social care they need. The study’s recommendation emphasized the need to address issues of poverty, inequality, and gender inequality as well as make sure that Nigeria’s national and sustainable development policies and programmes must address the serious mental health problems that women and children currently face as well as those that will arise after the post-Covid-19 era.